Especies nuevas y filogenia de las abejas de fuego, oxytrigona (hymenoptera: apidae, meliponini) - González, Victor H.; Roubik, David W. (Instituto de Ecología, A.C., 2008)
We describe and illustrate three new species from Central America and northern South America, present descriptions for previously unknown males and queens, and explore the internal phylogeny of Oxytrigona. Oxytrigona chocoana sp. nov., the sister species of O. daemoniaca, is from the Chocó biogeographic region; O. huaoranii sp. nov., and O. isthmina sp. nov., from the Eastern Andes of Ecuador and Darién (Panamá), are much smaller than their sister species, O. mellicolor. Oxytrigona huaoranii exhibits unusual characters including a short fore femur with carinate inferior margin, and  striated basal propodeum. The male of O. isthmina primarily differs from O. mellicolor in having genitalia with an apically enlarged and strongly bent gonostylus. We also described the males of O. daemoniaca and O. mediorufa, and the male and queen of O. mellicolor. The taxonomic status O. mediorufa is revised; as here understood, this species is distributed only from Mexico to El Salvador. We obtained a single tree for Oxytrigona in a cladistic analysis of 18 morphological and five body coloration characters, which did not support the monophyly of the mulfordi and tataira groups. We also found variation in the gradular and distal margin shapes of the worker sixth sternum, which were useful in the taxonomic analysis. Such characters have not yet been used in the systematics of Meliponini, and we hope to draw more attention to and encourage future phylogenetic studies using these characters. We also present an identification key for the species.